First Prize in International Competition Award Solo Exhibition - Antoniou, Klitsa (My University, 2026)
First Prize in International Competition. Award Solo Exhibition: Golden Lane Estate; Past, Present, and Future: A Design, Art and Community Legacy International Competition, London
Keywords: Arts and entertainment